Synthesis, Characterization and Antibacterial Activity of Some Schiff Bases of 2-Amino-3-(N-Tolyl Carboxamido)-4,5-Trimethelene Thiophenes - Mohan, S.; Saravanan, J. (Asian Journal of Chemistry, 2010)
2-Amino-3-(N-tolyl carboxamido)-4,5-trimethelene thiophenes (1-III) were synthesized by Gewald reaction. Later, the compounds I-III were treated with ten different substituted aryl aldehydes to yield thirty new Schiff bases (Ia–j to IIIa–j). The compounds were characterized by spectral data and were screened for antibacterial activity. Some of these Schiff basis exhibited promising activity.